Motivations and obstacles for adverse drug reactions reporting among healthcare professionals from the perspective of Lewin’s force field analysis theory: analytic approach - Elkalmi, Ramadan Mohamed Mahmod; Al-lela, Omar Q; Jamshed, Shazia Qasim (OMICS Publishing Group, 2014)
Spontaneous Adverse Drug Reactions (ADRs) reporting system is considered the back-bone for any pharmacovigilance system. Within this context, active Involvement of healthcare professionals is very crucial to improve the rate and quality of ADRs reporting. Despite the various techniques that have been adopted in order to improve the rate and quality of ADR reporting, there is a decline in the rate of ADRs notification. Under-reporting of ADRs is well-recognized phenomena associated with the almost all of pharmacovigilance systems around the world. Many logistic and personal barriers to ADRs reporting among healthcare professionals including resistance to change have been reported. This commentary focuses on the problem of resistance to change towards ADR reporting and the possibility of applying theory of Force Field Analysis (FFA) to overcome the problem of under- reporting among these professionals